(3CLhHI GdeSGFd GdejGaGQbjGJs - (3GdTQja GdeQJVj , CHh GdbGSe,J (B436 (3g` s ((3eMeO Hf GdTjN WGgQ GdSeGhi s)
(3ChdgG (B:s
(3fMf CWGd Gddg HbGA SjOfG GdTQja GdCLd GdeQJVi Yde GdOi s
(3BNQgG (B:s
(3EfeG Led dge YhVkG GdUObI aGfeG UfYhg ai HYV GdCReGf MdJ dge GdUObI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdChdis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B81s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis